Comparative Analysis of Physical Activity Detected via an External Accelerometer and Cardiac Implantable Electronic Devices - Chen, Chun-Kai; Cheng, Li-Ying; Hsu, Shan-Wei; Liao, Min-Tsun; Ku, Po-Wen; Liu, Yen-Bin (Frontiers in Cardiovascular Medicine, 2022)
Background: Physical activity (PA) has become an important health issue for decades. Cardiovascular implantable electronic devices (CIEDs) have built-in PA-recording functions. We aimed to compare PA measurements using an external accelerometer (ActiGraph GT3X+) and internal accelerometers (Abbott, Biotronik, and Medtronic CIEDs). Methods: This was a prospective, single-center observational study. The device-measured 7-day average PA was collected, and GT3X+-measured 7-day average PA was used as the gold-standard, including all daily observations of activity. Pearson’s correlation coefficients were used to compare the correlations between GT3X+-measured and CIED-measured PA. Bland-Altman plots were used to analyze measurement agreement, and intraclass correlation coefficients were used to analyze reliability. Results: In total, 720 patients treated with CIEDs were surveyed between November 2020 and April 2021, 60 of them were analyzed after patient screening by our protocol. Each manufacturer included 20 patients for the final analysis. The CIED-measured PAs of Abbott, Biotronik, and Medtronic were 3.0±1.5, 2.6±1.8, and 3.8±2.5 h per day, respectively; the GT3X+-measured PAs were 6.9±2.8, 6.0±2.4, and 6.4±2.5 h per day, respectively. Moderate and significant correlations were found in patients using Abbott, Biotronik, and Medtronic CIEDs (r=0.534, p=0.015; r=0.465, p=0.039; r=0.677, p=0.001, respectively). Bland-Altman plots and intraclass correlation coefficients both showed a significant correlation and reliability between the average PA measured by GT3X+ and CIEDs (hours per day). Conclusion: Although the PA recording function of CIEDs includes a single-axis accelerometer, it has a moderate correlation compared with the triaxial accelerometer of the GTX3+. However, CIEDs seem to underestimate PA for 3–4 h compared to the GTX3+.